Malvaceae from Serra do Lenheiro, Minas Gerais, Brazil - Maria Tereza Rodrigues Costa; Massimo Giussepe Bovini; Lívia Lara Alves; Gislene Carvalho de Castro; Marcos Sobral (Rodriguésia, 2023)
Abstract We present a taxonomic treatment of the Malvaceae from Serra do Lenheiro, a montane range in the municipality of São João del-Rei, Minas Gerais, Brazil, in order to contribute to the knowledge of this family and the state’s flora. Eleven genera and twenty-nine species were recorded. Sida, Pavonia and Peltaea are the richest genera. Among the recorded species, nine are considered as ruderal and ten are endemic of Brazil. Three species have São João del-Rei as the type-locality. Analytic keys, morphological descriptions, photographic plates and comments about the treated species are presented. Illustrations are presented for two species: one has no iconography in Brazilian studies for Malvaceae (Sida plumosa) and one has only poor iconographic representations (Sida viarum).